The image analysis of colour changes of different human tissues in the relation to the age. Part 2: practical applicability - Pilin, A; Pudil, F; Bencko, V (Soudni lekarstvi, 2007)
The method of image analysis of intervertebral disc, Achilles tendon and rib cartilage was applied for assessment of colour changes of these tissues in the relation to the human age. It was proved that colour of tested tissues changes with age which is most obvious on rib cartilage and intervertebral disc, while Achilles tendon does not display important changes. The parameters MeanBlue, MeanSaturation and MeanBrightness are the best for age estimation based on colour analysis.
Keywords: stárnutí; Ribs; meziobratlová ploténka; spektrofotometrie; Spectrophotometry; Aging; Cartilage; Forensic Pathology; Color; lidé; Achillova šlacha; Humans; Intervertebral Disc; Achilles Tendon; žebra; soudní patologie; chrupavka; barva